Investigation of the Potential Harnessing Tidal Energy in Malaysia - N. A., Mohd Yusoff; Noor Lina, Ramli; Mohd Rusllim, Mohamed (2015)

(untitled)
Tidal energy has been recognized as one of the promising technologies for future electricity generation for its predictability as compared to solar and wind energy, yet traditionally it has been renowned as a technology that's relatively needed detail analysis for availability sites identification and cost. This paper presents an analysis of potential harnessing tidal energy for a country that has low tidal ranges like Malaysia. Tides Table Malaysia 2014 published by National Hydrographic Centre Malaysia has been used in identifying potential sites for harnessing tidal energy in Malaysia. The data are tabulated in monthly and the most potential site for harness tidal energy is presented in hourly versus the height of water for every each of coastal area in Malaysia for better comparison with the results shown.